Inovasi Pemahaman Pendekatan Tafsir Perspektif Aksin Wijaya: Apresiatif-Kritis Dalam Mengungkap Aspek Keterbaruan Tafsir Maqasidi - Firdaus, Nadya Fitri Firdaus; Firdaus, Nadya Fitri; Fahma, Nuzila Addina; Yardho, Moh. (Al-Misykah: Jurnal Studi Al-qur'an dan Tafsir, 2024)
Nowadays, the study of tafseer is increasingly in the spotlight of various researchers/academics. Among the objects of tafseer studies that are widely discussed is the maqasidi interpretation approach. One of the researchers/academics who pay special attention to maqasidi interpretation is Aksin Wijaya. According to him, maqasidi interpretation is classified as a relatively new approach is in the study of the Qur’an. This is because this approach is in the “process of becoming”. In other words, maqasidi interpretations does not yet have its own strength/characteristics that distinguish it from other types of tafseer. Therefore, maqasidi has advantages and disadvantages. For Aksin, the advantages shold be appreciated, while the shortcoming need to be criticized. This appreciative-critical step is intended to strengthen the footing of maqasidi interpretation so that it is able to contest with various other variants of tafseer. The purpose of this research is to determine Aksin Wijaya’s paradigm in studying maqasidi interpretation. This research is qualitative and uses library research analysis. The results show that the adventage of maqasidi interpretation is that it is a moderate alternative that is able to mediate between textual-scriptualist and liberal-substansialist interpretations. The shortcomings are seen in the fact that maqasidi interpretation is in the process of “becoming”, so it is not yet established in terms of theology, epistemology and hermeneutics, especially in terms of its probability in revealing God’s intentions objectively.